Hypokalemia as a sensitive biomarker of disease severity and invasive mechanical ventilation requirement in COVID-19 pneumonia: a case series of 306 Mediterranean patients (2020)
Objectives Serum levels of potassium (K+) seem significantly lower in severe SARS-CoV2 infection, with an unknown clinical translation. The objective was to investigate whether hypokalemia acts as a biomarker of severity in COVID-19 pneumonia, and associates with major clinical outcomes. Methods Retrospective cohort study of inpatients with COVID-19 pneumonia (March 3 - May 2, 2020). Patients were categorized according to nadir levels of K+ in the first 72 hours of admission: hypokalemia (K+ ≤3.5 mmol/L) and normokalemia (>3.5 mmol/L). Main outcomes were all-cause mortality and need of invasive mechanical ventilation (IMV), analyzed by multiple logistic regression (OR; 95%CI). Results 306 patients were enrolled. Ninety-four patients (30.7%) had hypokalemia, showing at baseline significantly higher comorbidity (Charlson index ≥3, 30.0% vs. 16.3%)(p=0.02), CURB65 scores (1.5(0.0-3.0) vs. 1.0(0.0-2.0))(p=0.04), and some inflammatory parameters. After adjustment for confounders, hypokalemia was independently associated with requiring IMV during the admission (OR 8.98; 95%CI 2.54-31.74). Mortality was 15.0% (n=46) and was not influenced by low K+. Hypokalemia was associated with longer hospital and ICU stay. Conclusions Hypokalemia is prevalent in patients with COVID-19 pneumonia. Hypokalemia is an independent predictor of IMV requirement and seems to be a sensitive biomarker of severe progression of COVID-19.